Application of Contextual Teaching and Learning (CTL) Learning Model assisted by Spinning Wheel Media to Improve Social Science Learning Outcomes of Grade IV Students - A'ini, Qurrotul; Erwandi, Rudi; Krisnawati, Yuni (Global Education Journal, 2025)
This study aims to determine the completeness of social studies learning outcomes of grade IV students of SD Negeri 47 Lubuklinggau after applying the Contextual Teaching and Learning (CTL) Learning Model Assisted by Media Spinning Wheel. This type of research is quantitative research. With a research sample of 25 students in grade IVB of SD Negeri 47 Lubuklinggau. The data collection techniques used in this study are tests, observations, interviews and documentation. The data analysis techniques in this study are to determine the standard and mean deviation, normality test (Chi squared) and hypothesis test (t-test). The result of this study is that in the post test hypothesis calculation can be obtained tcount = 1.842 and ttable = 1.711. The tester's criterion is that if the tcount ≥ ttabul, then Ho is rejected and Ha is accepted. If the tcount ≤ the table, then Ho is accepted and Ha is rejected. Based on the calculation of the hypothesis test above, it was obtained that the tcount of ≥ ttable (1,842 ≥ 1,711) was rejected and Ha was accepted. In other words, the hypothesis proposed in this study can be accepted as true, meaning "The learning outcomes of grade V students in the learning of IPAS SD Negeri 47 Lubuklinggau after the implementation of the CTL learning model assisted by Media Spinning Wheel are significantly complete.